2014
DOI: 10.1128/aac.00099-14
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem-Resistant Klebsiella pneumoniae Strains Exhibit Diversity in Aminoglycoside-Modifying Enzymes, Which Exert Differing Effects on Plazomicin and Other Agents

Abstract: eWe measured in vitro activity of plazomicin, a next-generation aminoglycoside, and other aminoglycosides against 50 carbapenem-resistant Klebsiella pneumoniae strains from two centers and correlated the results with the presence of various aminoglycoside-modifying enzymes (AMEs). Ninety-four percent of strains were sequence type 258 (ST258) clones, which exhibited 5 ompK36 genotypes; 80% and 10% of strains produced Klebsiella pneumoniae carbapenemase 2 (KPC-2) and KPC-3, respectively. Ninety-eight percent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
71
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 36 publications
7
71
1
3
Order By: Relevance
“…Only 2 of the 58 isolates that harbored the aac(6=)-Ib gene alone expressed phenotypic resistance to amikacin, although it has been reported that aac(6=)-Ib confers resistance to both antibiotics (3). These observations were consistent with previous studies where, despite the possession of aac(6=)-Ib, low amikacin MICs have been reported for E. coli and K. pneumoniae strains (14,17). In our study, moreover, there was a statistically significant relationship (P Ͻ 0.01) between the presence of an aac(6=)-Ib gene and an amikacin MIC of Ͼ8 mg/liter.…”
supporting
confidence: 82%
See 3 more Smart Citations
“…Only 2 of the 58 isolates that harbored the aac(6=)-Ib gene alone expressed phenotypic resistance to amikacin, although it has been reported that aac(6=)-Ib confers resistance to both antibiotics (3). These observations were consistent with previous studies where, despite the possession of aac(6=)-Ib, low amikacin MICs have been reported for E. coli and K. pneumoniae strains (14,17). In our study, moreover, there was a statistically significant relationship (P Ͻ 0.01) between the presence of an aac(6=)-Ib gene and an amikacin MIC of Ͼ8 mg/liter.…”
supporting
confidence: 82%
“…PCR screening showed that aac(6=)-Ib was the most prevalent gene. Similar results have been reported by other authors (17,18). All strains with aac(6=)-Ib were tobramycin resistant.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…Tigecycline, aminoglycosides, and the polymyxins (polymyxin B and colistin) are currently the best treatment options for carbapenemase-producing strains (13). However, these strains also have the potential to develop resistance to these antibiotics (14)(15)(16).…”
mentioning
confidence: 99%